2022
DOI: 10.1109/access.2022.3157812
|View full text |Cite
|
Sign up to set email alerts
|

Performance Monitoring Counter Based Intelligent Malware Detection and Design Alternatives

Abstract: Hardware solutions for malware detection are becoming increasingly important as softwarebased solutions can be easily compromised by intelligent malware. However, the cost of hardware solutions including design complexity and dynamic power consumption cannot be ignored. Many of the existing hardware solutions are based on statistical learning blocks with abnormal features of system calls, network traffics, or processor behaviors. Among those solutions, the performance of the learning techniques relies primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, no procedure is perfect. In line with what Pattee et al (2022) point out regarding malware detection, most software can easily be detected by means of simple checks, but some are very similar to benign code and need to be handled more thoroughly.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, no procedure is perfect. In line with what Pattee et al (2022) point out regarding malware detection, most software can easily be detected by means of simple checks, but some are very similar to benign code and need to be handled more thoroughly.…”
Section: Discussionsupporting
confidence: 65%
“…These results are in line with previous findings (Waggoner et al, 2019) and with the fact that a small number of sources tend to generate large amounts of fake news (Allcott & Gentzkow, 2017; Axelrod & Hamilton, 1981). This is particularly relevant for businesses operating in online environments, such as social networks, e‐commerce platforms, and online service providers, as the identification of spammers’ profiles can enable the implementation of specific security protocols and antifraud algorithms that target certain groups (Pattee et al, 2022). That is, algorithms for identifying IP duplication could provide a list of IP addresses suspected of harboring spammers.…”
Section: Discussionmentioning
confidence: 99%
“…Pattee et al proposed a mechanism to complete the flow of hardware event collection, conversion of events to metadata for use in discrimination, and malware detection on the hardware, similar to our proposed MDM [22].…”
Section: Related Workmentioning
confidence: 99%
“…However, the more detailed architectural design for a dedicated accelerator provided efficiencies better for chip area, power, and processing time was required to be investigated. [30] 3.17 --Malware based on behavior chains [31] -90s -PMC-based malware detection [35] 12.5 6.825ms -MALDC [36] -20s 10% Proposed MLLD-MDQL 12.85 25.525ms 60-600kB…”
Section: Comparative Analysismentioning
confidence: 99%
“…The results showed that the developed model improved the accuracy for the effective classification but failed to discover the new malware effectivel and thus, Pattee et al [35] developed an intelligent malware detection and design alternatives for performance monitoring counter. The developed model improved the importance of selecting the features for malware detection that showed statistical differences among the malware workloads and benign workloads were characterized on the basis of information from counters performances.…”
Section: Introductionmentioning
confidence: 99%